Group of Community-Based Tourism Awareness (Pokdarwis) Strategies in Addressing Conflicts in Utilization and Conservation of the Environment - Sulistyo, Ari; Rijanta, R.; Hadna, Agus Heruanto; Giyarsih, Sri Rum (Forum Ilmu Sosial, 2023)
The use of natural resources is very prone to conflict because of the friction between economic motives (utility) and conservation motives (protection). This potential conflict also occurs in the use of Mount Sewu UNESCO Global Geopark where the main development is through the tourism sector. This research aims to find out the strategies of the people who are members of the Tourism Awareness Group (Pokdarwis) in dealing with potential conflicts over use and environmental conservation in the Gunung Sewu UNESCO Global Geopark area. This research is a qualitative study with a descriptive approach. The locations of this research are in Gunungkidul Regency, namely the Nglanggeran Ancient Volcano Geosite, the Pindul Cave Geosite, and the Siung Beach Geosite. This area was chosen as a representation of 2 (two) other districts in the Gunung Sewu UNESCO Global Geopark area, namely Wonogiri District and Pacitan District. In this research, researchers used participatory observation where data was collected through observation and sensing where the observer or researcher was truly involved in the respondent's daily life. The results of this research show that there is physical and non-physical damage as a result of the use of geoparks in the tourism sector. Physical damage includes damage to karst rocks, soil erosion, damage to vegetation, decreased water absorption capacity, pollution of rivers and seas, and vandalism. While non-physical damage includes economic inequality and social conflict. As a response to this damage, Pokdarwis adopted strategies and policies, including holding environmental cleanup work, building tourist attractions with environmentally friendly materials, installing signs calling for environmental cleanliness, limiting the number of tourist operators, managing waste in an integrated manner, building alternative tourist attractions, and forbid investors from entering. Based on a literature review, these strategies are classified as grassroots innovations. This research also strengthens the theory that community participation or empowerment is one of the best strategies in dealing with conflicts over environmental use and conservation.